Penerapan Model Pembelajaran Kooperatif Tipe STAD Dengan Teknik Jari Sakti Untuk Meningkatkan Hasil Belajar Matematika - Awaludin, Asep (Universitas Sebelas Maret, 2020)
The low results of mathematics learning achieved by grade VI students of SD N Pamedaran 01. This is due to the low ability of students in multiplication mastery. Therefore, the purpose of the problem raised in this study is